An operations analysis using aggregate planning on the loading process of Comfoods - Capistrano, Cesar Lorenzo G.; Lagonera, Maria Jacinta K.; Mirasol, Ian Vincent O.
Commonwealth Foods, Inc. delivers three products - coffee, chocolate, and biscuits- to various retailers such as Puregold, Robinson's and SM. It has been observed from recorded purchase orders and invoices from SM that 25,326 cases for the month of December 2015 are not loaded into the trucks for delivery. Currently, they have eight regular workers that are assigned to loading in the coffee plant which is where the SM-bound trucks depart from. The unloaded cases are caused by an insufficient loading capacity which incurs loss in sales for the company amounting to Php 7,438,246.20. By forecasting demand and determining the appropriate number of cases each loader can load, possible aggregate plans can be formulated to significantly improve loading capacity and reduce costs.